Pengaruh game online terhadap kualitas belajar pada remaja dan upaya pencegahannya - thansyah, dhonan (Maliki Interdisciplinary Journal, 2024)
In the current millennium era, adolescents are facing significant challenges related to the usage of online games, which potentially impact their learning quality. Despite technology providing easy access to information and recreation, online gaming addiction has become a concerning issue. Research findings indicate that the impact of online games on students’ academic performance results in decreased academic achievements, mental health disturbances, and limited social interaction. Effective preventive measures are essential to address this issue. Strategies such as attention switching, dissuasion, education, parental monitoring, and resource restriction can help reduce the level of online gaming addiction among adolescents.